(untitled) (Collection of scientific works «Modern structures of metal and wood», 2024)
On the basis of the literature review, trends in the development of studies of engineering protection of critical infrastructure objects were revealed. The review of scientific works revealed the direction of improving the physical and mechanical properties of building protective structures. It is noted that large-scale experimental and theoretical studies of reinforced concrete structures and reinforced concrete protective plates with the use of fiber were carried out. Experimental and theoretical studies of reinforced concrete protective structures on the impact of rockets and the subsequent explosion have been identified and summarized. The study of structures using different materials is shown. It was determined that one of the promising directions is the use of multilayer composite structures. The results of experimental studies by various authors were analyzed and it was concluded that air damage impacts should be classified into 4 categories: an impact, a soft impact, a hard impact of a projectile with a steel shell; a semi-solid impact is the impact of a missile whose outer shell is made of a composite material or a thin-walled titanium alloy. The authors also draw attention to the possibility of studying an all-plastic impact - the impact of a concrete-piercing warhead of a missile with a 20-22 mm titanium body, the impact is accompanied by the development of plastic deformations in the shell during penetration into the composite reinforced concrete layer. An overview of the main methods of calculating the penetration of combat units during an impact on defensive structures was carried out. The formulas of the main methods are based on the results of experimental and theoretical studies NDRC. Effects of impact and explosion. Summary Technical Report Division 2, 1, National Defense Research Committee, Washington, DC, 1946". A generalized conclusion is made regarding the use of the modified NDRC (USA) method for evaluating experimental studies.